Policy paradox in Africa : strengthening links between economic research and policymaking - Ayuk, Elias; Marouani, Mohamed Ali (Africa World Press ; International Development Research Centre, 2007)
"During the past three decades, the African continent has faced a wide range of challenges, amongst which are those related to its economic development. Finding solutions to these development challenges has received considerable attention within the international donor community, regional organizations and the individual countries themselves. On the international front, the Millennium Development Goals set a timeline of targets to be attained by 2015. The Bretton Wood institutions, in particular, and other initiatives such as the Commission for Africa that British Prime Minister Tony Blair launched in 2004 have played varying roles in the search for appropriate answers. Structural adjustment programmes, poverty reduction strategies, plans for debt cancellation and the G8 promise to focus on Africa are just some of the examples of the effort. A key issue associated with addressing the continent's development problems has been the degree of local participation in the design of these solutions. While it is recognized that homegrown solutions have a higher probability of success than those developed off the continent, the lack of availability of local capacity has been identified as a major stumbling block. However, even when there is the capacity available, policy-makers have not adequately exploited it, generally preferring to defer to the opinion of external foreign consultants. Strengthening the capacity of economic research institutions so that they can play an effective role in the design of economic policy has been one of the key objectives of the Secretariat for Institutional Support for Economic Research in Africa (SISERA). SISERA was established in 1997 as a Secretariat of the International Development Research Centre (IDRC). It provided technical and financial support to economic research centres in sub-Sahara Africa (SSA) so that they can undertake policy-relevant research with the goal of influencing economic policy-making. In January 2005, the Secretariat organized an international conference in Dakar, Senegal, during which participants from key economic think tanks presented their experiences in the policy development process in Africa. Of particular interest was the role of economic research and economic researchers in policy-making. The authors examine the extent to which economic policies that are formulated in the sub-continent draw from research based on local realities and undertaken by local researchers and research networks in Africa. Other relevant issues that received attention include: the main channels and mechanisms through which economic research influences policy-making in Africa; the degree to which policy-makers rely on economic research in their decision making; the level of incentives for economists to feed the policy debate; and the impact of donor behaviour on the policy-research relationship. The participation of policy-makers at this conference provided a unique opportunity for vibrant discussions. The presentations were supplemented with roundtable discussions that allowed exchange of ideas. This book brings together selected papers that were presented at the conference. These papers are based on the individual experiences of the researchers and their institutions in working with policy-makers on policy relevant issues with the goal of providing useful input in the development of economic policy. An important conclusion emerging from the available evidence is that there is a disconnect between policy-making and economic research. Research institutions have to build their credibility, develop a communication strategy and remain attentive to the needs of the policy makers. The underlying reason for remaining attentive to the needs of policy-makers is the fact that the link between policy research and policy-making is non-linear. Researchers must therefore be flexible and agile in the timing of their interventions. There is an urgent need for a concerted effort by all stakeholders involved in policy development in Africa. The economic researchers and institutions have the necessary skills to provide useful input into the policy debate. They must continue to undertake credible research that addresses the needs of the policy-makers. Policy-makers should understand that foreign consultants do not have any comparative advantage over local researchers. As for the donor community, they must strive to draw more from the local research community than they have done in the past. Recent developments seem to indicate that the various stakeholders are becomingly increasingly conscious of the need to work together if policies in Africa are to reflect the needs of the countries for which and in which they are being developed and applied. These efforts must be pursued so that domestic policies can provide the necessary impetus for economic development. The following pages offer some invaluable suggestions for how that can be done."--Preface